The Influence Of Participative Leadership Style On The Performance Of Labae Village Officials - Reski Rahmat Yuliana; Mansur Mansur; Asmajaya Asmajaya (GENTARA: management and accounting research, 2026)
This study aims to determine and analyze the effect of participative leadership style on the performance of village officials in Labae Village, Citta District, Soppeng Regency. Participative leadership is viewed as a leadership approach that can enhance subordinate involvement in decision-making, strengthen two-way communication, and foster a sense of responsibility and cooperation within village government organizations. This research employs a quantitative approach using descriptive and correlational methods. The research population consists of all village officials in Labae Village, totaling 14 individuals, with total sampling applied as the sampling technique. Data were collected through Likert-scale questionnaires, observation, and documentation, and then analyzed using descriptive statistics, Pearson correlation tests, and simple linear regression with the assistance of SPSS software. The results indicate that participative leadership style has a positive and significant effect on the performance of village officials, as shown by a significance value of less than 0.05 and a strong level of relationship. These findings suggest that the better the implementation of participative leadership by the village head, the higher the performance of village officials, as reflected in improved work discipline, responsibility for tasks, teamwork capability, and quality of public services. Therefore, the application of participative leadership is considered crucial for improving village officials’ performance and supporting the realization of effective, transparent, and professional village governance